Models of Protection Against Recidivism in Justice-Involved Adults With Mental Illnesses - Lowder, Evan Marie (Criminal justice and behavior, 2017)
Protective factors may play an important role in the assessment, treatment, and supervision of adult offenders with mental illnesses. However, little is known regarding associations between protective factors, risk factors, and recidivism in this population. In research with adolescents, five models describing these associations have been proposed and tested: (a) Compensatory, (b) Buffer, (c) Challenge, (d) Protective-Protective, and (e) Mediation. This study evaluated these models of protection against recidivism in a sample of justice-involved adults with mental illnesses (N = 550). Risk and protective factors were operationalized using Short-Term Assessment of Risk and Treatability (START) assessments. Results showed consistent evidence for the Compensatory model, where risk and protective factors were independently associated with recidivism. In contrast, results failed to provide evidence supporting the other four models. Findings underscore the importance of both risk and protective factors in the assessment, treatment, and supervision of adult offenders.